Penentuan Struktur Regional Cekungan Sumatera Utara Area Prospek Langsa (UPEJ Unnes Physics Education Journal, 2022)
The North Sumatra Basin is a backarc basin with good hydrocarbon potential. Exploration of hydrocarbons in oil and gas basins in Indonesia is carried out with new reservoirs where oil and gas basins are found in the tertiary layer. Determination of the regional structure in the Langsa area aims to produce a modeling of the geological structure of the North Sumatra Basin. The method used in this research is 3D modeling which is supported by secondary data in the form of gravity data GGMplus 2013 research area obtained from the official website of BGI (Bureau Gravimetric International). The initial model which was compiled based on geological research and has been carried out mathematical calculations on the ABL data is used as a reference in the inversion stage. The results of the research that have been carried out are suspected that the subsurface structure of the Langsa area in the southwest is dominated by igneous rocks with a density value of 2.127 gr/cm3 to 3.17 gr/cm3 which can be seen from the results of high gravity anomaly values, while rocks with low density values 1,087 gr/cm3 to 1,873 gr/cm3 dominantly scattered throughout the study area which are sedimentary rocks. The presence of faults in this area is a pathway for hydrocarbon migration from the source rock to the reservoir.